A View from Academic Administrators on the Characteristics of Future University - Jusoh, Ahmad; Zulkifli, Anis Syahira; Rasli, Amran Md.; Munir, Yasin (International Journal of Economics and Financial Issues, 2015)
Present study is an attempt to investgate a view from academic administrators on the characteristics of future university. A stratified sampling technique is applied according to the structure of the university, i.e faculty and registrar office/university administration. The heads of departments are targeted to collect the responses in five Malaysian public universities, which attained ‘research university' status, i.e Universiti Teknologi Malaysia (UTM), Universiti Kebangsaan Malaysia (UKM), Universiti Putra Malaysia (UPM), Universiti Malaya (UM) and Universiti Sains Malaysia (USM). Factor analysis is used and nine components (dynamic environment, democratization of knowledge, sustainable infrastructure, global mobility, technology advancement, institutional autonomy, teaching-research balance, smart partnership, and abundant resources) were extratced statistically significant. Current study highlights an important research agenda for future studies and will contribute in existing body of knowledge by fortifying the current debate on the subject of education and future university. Keywords: Future university; Malaysian Public Universities; Factor Analysis JEL Classifications: M00